1986
DOI: 10.1017/s0317167100036659
|View full text |Cite
|
Sign up to set email alerts
|

Serial Recordings of Multimodality Evoked Potentials in Multiple Sclerosis: A Four Year Follow-Up Study

Abstract: ABSTRACT:Pattern reversal visual, brain-stem auditory, and short latency median nerve somatosensory evoked potentials (EPs) were evaluated in a prospective study over 4 years in 20 patients with clinically definite sclerosis (MS). Standardized neurological examinations were done at regular intervals and correlated with EP findings. The highest incidence of EP abnormalities occurred in the visual system followed by the somatosensory and auditory systems. Clinical relapse was usually accompanied by EP deteriorat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

1987
1987
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 22 publications
1
9
0
Order By: Relevance
“…Our results showed no difference between cytokine levels of male and female patients similar to results of Eikelenboom et al (8). Unilaterally or, more frequently, bilaterally prolonged VEP P100 latencies were present in 65.0% of our patients, which was similar to results of previous studies (1,4,5). Evoked potentials are frequently used to confirm the diagnosis of MS.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results showed no difference between cytokine levels of male and female patients similar to results of Eikelenboom et al (8). Unilaterally or, more frequently, bilaterally prolonged VEP P100 latencies were present in 65.0% of our patients, which was similar to results of previous studies (1,4,5). Evoked potentials are frequently used to confirm the diagnosis of MS.…”
Section: Discussionsupporting
confidence: 92%
“…Various studies investigating relationships between the evoked potential latencies and the disability scores in MS gave opposite results. Some studies demonstrated that the expanded disability status scale (EDSS) scores increased parallel to delays in visual evoked potentials (VEP) (2,3), however others found no correlation between disability scores and change in the VEP latencies (4,5). Magnetic resonance imaging (MRI) often demonstrates new lesions independent of clinical status (6).…”
Section: Introductionmentioning
confidence: 99%
“…Stable patients are electrophysiologically stable [9,24], whereas progression of disability seems to be associated with a progressive increase in latency [9,30]; no or poor correlations can be found with clinical symptoms [1,2,12,24]. In a long-term followup of chronic progressive azathioprine-methylprednisolone-treated MS patients, Nuwer et al [20] were able to find a correlation between latency changes and clinical outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the information contained in EPs may not be fully exploited by insensitive scales, such as worse-better-unchanged. Latency measurements seem to be useful in long-term follow-up [20] and a clinicoelectrophysiological correlation has been found in relapsing-remitting and progressive MS patients using an arbitrary EP abnormalities scale based on latency and waves extintion [4,12]. Severeal lines of evidence strongly suggest that a conduction block (whose EP marker is waveform distortion: [I0]), rather than conduction slowing accounting for increased latency is related to clinical deficits [21,23,31].…”
Section: Discussionmentioning
confidence: 99%
“…Similar degrees of improvement in CMCT have also been documented with clinical improvement in response to physiotherapy (Kandler, 1990) and in patients who improve without treatment for a relapse (Sahota et al, 2005), making a specific effect of corticosteroids on neural excitability less likely. VEP latencies have been reported both to improve (Brusa et al, 2001) and to remain static (Compston et al, 1987;de Weerd and Jonkman, 1982) in patients who have improved clinically; SSEP latencies have not been shown to change longitudinally (de Weerd, 1987;Iragui et al, 1986;La Mantia et al, 1994;Smith et al, 1986) in patients who have improved clinically, with or without steroid therapy. Kidd et al (1998) studied a group of 20 patients with progressive MS longitudinally and demonstrated that clinical progression over the course of 1 year was seldom associated with progressive prolongation in CMCT, unless there were also new spinal cord lesions which developed over the same timeframe.…”
Section: Tms In Longitudinal Disease Assessmentmentioning
confidence: 99%